PENANAMAN NILAI NILAI TASWUF PADA PENDIDIKAN KARAKTER SISWA SMA AL-RIFAI’E GONDANGLEGI MALANG - Sherly Ana Masuda (VICRATINA, 2019)
Tasawwuf or mysticism or suluk is science that studies the way a person can be as close as possible to his God. The main purpose and mystical essence is to be in the presence of God. And get a direct relationship that is realized with God. Broadly speaking, tasawwuf is also very important which is useful as a guardian of morals as well as the character of the nation's life which has eroded the flow of globalization. The Qur'an and Hadith which are the most important sources in forming one's Ketasawwufan to Allah SWT, provide solutions that can be used in reference to form the method of learning akhlaq or tasawwuf itself, so that in another lesson one of the leaders of this nation says how important alqur 'an and hadith in shaping relationships one becomes closer to his God. where when someone wants a change in bad character towards a better one, the only way is to see alquran and hadith Keywords: value of tasawwuf value, character education